Uprizarjanje moškosti v predvolilni predsedniški kampanji 2012 - Crnović, Deja (Družboslovne razprave, 2014)
The article examines the presidential campaign of Borut Pahor prior to the 2012 presidential elections by analysing its television and online coverage. Borut Pahor then temporarily took up 46 different occupations, mostly involving manual labour, thus also performing a different masculinity than the one he performed before the election. Due to the mediatisation of politics and eventisation of his campaign, Borut Pahor changed from a new man who is mostly concerned with his looks to a working-class man who puts morality, responsibility and hard work first. By focusing on his competence as a manual worker, Pahor simultaneously helped depoliticise the presidential function.
Keywords: Pahor, Borut, 1963-; Presidential elections; Predsedniške volitve; Election campaigns; Mass media; Volilne kampanje; Množični mediji; Masculinity; Moškost; Slovenia; Slovenija; politics; politika; predvolilna kampanja; promocija; Promotion